A rela????o entre satisfa????o e respostas comportamentais e de inten????o dos consumidores: os efeitos indiretos do envolvimento e reputa????o - Fernandes, Aleixo (2016)
This thesis seeks to explain how moderators of satisfaction - reputation and involvement - act on the willingness to pay more and loyalty. These moderators were chosen because they are recognized in the literature as components which relates with cognitive and emotional elements that make up the satisfaction. The purpose of this study is to explain the influence of reputation and involvement variables on the relationship between satisfaction (independent), loyalty to the brand, and the willingness to pay more (dependent) for after-sales service. The gap that this study seeks to fill is to demonstrate to what extent consumer satisfaction with after-sales service contributes important aspects to the companies' market results. To this end, it aims to answer how the company's reputation and consumer involvement influence the effect of consumer satisfaction on loyalty and the desire to pay more. This quantitative study uses a survey to obtain data. After the collection, regressions were performed with the objective of verifying how the interaction between the variables occur. Of the 9 hypotheses constructed, 4 were confirmed, 2 were partially confirmed and 3 could not be verified. An unexpected result is that the response of the willingness to pay more as a function of satisfaction was linear, whereas the theory suggests that it should be non-linear. At the end, limitations, academic and managerial contributions as well as suggestions for future research are presented.